2012
DOI: 10.1111/j.1365-2389.2012.01463.x
|View full text |Cite
|
Sign up to set email alerts
|

Salinity decreases dissolved organic carbon in the rhizosphere and increases trace element phyto‐accumulation

Abstract: Soil degradation processes, such as organic matter (OM) depletion, accompanied by metal contamination and salinization are becoming a serious threat to crop production and human food security. A glasshouse study was conducted to assess a factorial combination of salinity (0, 20, 40 and 60 mm NaCl) and cadmium (Cd) (0.3, 2.5 and 5.4 mg Cd kg−1) in organic soil (>90% OM) and their influence on dissolved organic carbon (DOC) in the rhizosphere and phyto‐accumulation in radish (Raphanus sativus L. var. sativus). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Salinity not only accelerates the decrease of soil OM but also increases the accumulation of harmful trace elements in plants (Ondrasek et al, 2012), inhibits the microbial activity in soils (Setia et al, 2014), and delays the decomposition of soil organic residues (Peinemann et al, 2005). Soil properties deteriorate as OM diminishes (Wong et al, 2010) because soil OM is important for nutrient recycling, cation exchange capacity, water holding, and structure stability.…”
mentioning
confidence: 99%
“…Salinity not only accelerates the decrease of soil OM but also increases the accumulation of harmful trace elements in plants (Ondrasek et al, 2012), inhibits the microbial activity in soils (Setia et al, 2014), and delays the decomposition of soil organic residues (Peinemann et al, 2005). Soil properties deteriorate as OM diminishes (Wong et al, 2010) because soil OM is important for nutrient recycling, cation exchange capacity, water holding, and structure stability.…”
mentioning
confidence: 99%
“…The enhancement of Cd uptake by co-planted soybean in contaminated soils under saline condition might be attributed to the increase of the labile Cd concentration pool (Phytoenrichment) in the shared rhizosphere ( Figure 3) and reduction of Cd uptake by co-occurred purslane (Figure 4). Ondrasek et al (2012) reported that salinity, induced by NaCl, increased Cd solubility in the rhizosphere, as a consequence of dissolved organic carbon (DOC) diminution. They mentioned that salinity-induced DOC reduction might decrease Cd-DOC complexation, and consequently increase the uptake of free Cd ion (Cd 2+ ) by plant.…”
Section: Resultsmentioning
confidence: 99%
“…The role of organic matter in the control of metal ions was investigated by Ondrasek et al (2012) in a study of the effect of salinity on dissolved organic matter (DOM) in the rhizosphere of radish and consequently on solubility and phyto‐accumulation of Cu, zinc and cadmium. The depletion of DOM with excessive salinity favoured desorption of these potentially hazardous trace metals from the soil organic colloids, thus enhancing their solubility/mobility and therefore possible accumulation in food crops.…”
Section: Physico‐chemical Interactionsmentioning
confidence: 99%